Artist Thuyên extended interview - Son Nguyen (22474540) (2025)
Artist Thuyên's extended interview with Co-I Phạm Thanh Thôi. He discusses his artistic training, his mentor, living and working in an alleyway community, balancing work and family life, the current trend for retro signs as part of a wider nostalgic turn, and his hopes for the signpainting profession in future.